Advances in discontinuous numerical methods and applications in geomechanics and geoengineering : proceedings of the 10th International Conference on Advances in Discontinuous Numerical Methods and Applications in Geomechanics and Geoengineering, ICADD 10, Honolulu, Hawaii, 6-8, December 2011 /: proceedings of the 10th International Conference on Advances in Discontinuous Numerical Methods and Applications in Geomechanics and Geoengineering, ICADD 10, Honolulu, Hawaii, 6-8, December 2011. (©2012) - Unknown
No abstract available